Analyzing narrative : discourse and sociolinguistic perspectives - De Fina, Anna (Cambridge University Press, 2012)
"The socially minded linguistic study of storytelling in everyday life has been rapidly expanding. This book provides a critical engagement with this dynamic field of narrative studies, addressing long-standing questions such as definitions of narrative and views of narrative structure but also more recent preoccupations such as narrative discourse and identities, narrative language, power and ideologies. It also offers an overview of a wide range of methodologies, analytical modes and perspectives on narrative from conversation analysis to critical discourse analysis, to linguistic anthropology and ethnography of communication. The discussion engages with studies of narrative in multiple situational and cultural settings, from informal-intimate to institutional. It also demonstrates how recent trends in narrative analysis, such as small stories research, positioning analysis and sociocultural orientations, have contributed to a new paradigm that approaches narratives not simply as texts, but rather as complex communicative practices intimately linked with the production of social life"